Is Workfare Cost-Effective against Poverty in a Poor Labor-Surplus Economy? - Murgai, Rinku; Ravallion, Martin; van de Walle, Dominique (World Bank, Washington, DC, 2014)
Workfare schemes impose work requirements on beneficiaries. This has seemed an attractive idea for self-targeting transfers to poor people. This incentive argument does not imply, however, that workfare is more cost-effective against poverty than even poorly-targeted options, given hidden costs of participation. In particular, even poor workfare participants in a labor-surplus economy can be expected to have some forgone income when they take up such a scheme. A survey-based method is used to assess the cost-effectiveness of India's Employment Guarantee Scheme in Bihar. Participants are found to have forgone earnings, although these fall well short of market wages on average. Factoring in these hidden costs, the paper finds that for the same budget, workfare has less impact on poverty than either a basic-income scheme (providing the same transfer to all) or uniform transfers based on the government's below-poverty-line ration cards. For workfare to dominate other options, it would have to work better in practice. Reforms would need to reduce the substantial unmet demand for work, close the gap between stipulated wages and wages received, and ensure that workfare is productive -- that the assets created are of value to poor people. Cost-effectiveness would need to be reassessed at the implied higher levels of funding.